Zabezpieczenie tajemnicy partyjnej i państwowej w pracy aparatu PZPR w świetle przepisów wydanych w 1973 r. przez Komitet Wojewódzki PZPR w Lublinie - Czarnota, Tomasz (Komunizm: System - Ludzie - Dokumentacja, 2023)
Party apparatus of the Voivodeship Committee (hereinafter: KW) of the Polish United Workers’ Party (PZPR) in Lublin entered into force. Modeled on an analogous norm developed for use by state administration offices, it was a complex regulation of party activities in this sphere. It defined, among other things, procedures, physical security measures, and tools for accounting documents containing confidential information and the rules for their qualifications. Its resolutions were extended outside the KW PZPR apparatus, to the county committees (hereinafter: KP) of this party in Lublin province. They had to develop their own regulations adapted to their organizational structure. The application of these provisions was subject to a one-off inspection, which revealed the incomplete compliance with them. Further KP inspections were probably not effected by the termination of this party structure in 1975. These provisions retained the force.